2022
DOI: 10.3390/polym14153139
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity Enhancement in MCF-7 Breast Cancer Cells with Depolymerized Chitosan Delivery of α-Mangostin

Abstract: The application of α-mangostin (AMG) in breast cancer research has wide intentions. Chitosan-based nanoparticles (CSNPs) have attractive prospects for developing anticancer drugs, especially in their high flexibility for modification to enhance their anticancer action. This research aimed to study the impact of depolymerized chitosan (CS) on the cytotoxicity enhancement of AMG in MCF-7 breast cancer cells. CSNPs effectivity depends on size, shape, crystallinity degree, and charge surface. Modifying CS molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…This research succeeded in developing a targeted delivery system of hyaluronic acid-coated chitosan nanoparticles for the targeted delivery of alpha mangostin for breast cancer. Our findings showed that alpha mangostin loaded in our delivery system had a significant impact on MCF-7 cancer cells at a lower dose (IC 50 4.37 μg/mL) compared to free alpha mangostin (IC 50 5.27 μg/mL) or nanoparticles of alpha mangostin with chitosan carriers without a hyaluronic acid coating (IC 50 4.48 μg/mL, IC 50 6.7 μg/mL [ 27 ], IC 50 4.90 μg/mL [ 91 ]). The most conclusive findings of this study indicated that the developed alpha mangostin targeted nanoparticle delivery system can be used as an effective treatment for breast cancer by specifically targeting cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…This research succeeded in developing a targeted delivery system of hyaluronic acid-coated chitosan nanoparticles for the targeted delivery of alpha mangostin for breast cancer. Our findings showed that alpha mangostin loaded in our delivery system had a significant impact on MCF-7 cancer cells at a lower dose (IC 50 4.37 μg/mL) compared to free alpha mangostin (IC 50 5.27 μg/mL) or nanoparticles of alpha mangostin with chitosan carriers without a hyaluronic acid coating (IC 50 4.48 μg/mL, IC 50 6.7 μg/mL [ 27 ], IC 50 4.90 μg/mL [ 91 ]). The most conclusive findings of this study indicated that the developed alpha mangostin targeted nanoparticle delivery system can be used as an effective treatment for breast cancer by specifically targeting cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of water-soluble COS in the studied samples was determined according to the method of Herdiana et al [ 25 ]: the mixture of CS/H 2 O 2 solution was filtered on a quantitative filter paper with a pore size of 2 μm to collect the insoluble part of CS and dried to constant weight (m). The amount of COS dissolved in water (S) was calculated according to the following Formula (1) : …”
Section: Methodsmentioning
confidence: 99%
“…For example, drugs can be encapsulated within the chitosan matrix, loaded onto the surface of the nanoparticles, or attached to the surface of the nanoparticles via chemical linkers. The release rate of the drugs can be controlled by varying the size and charge of the nanoparticles or modifying the chitosan matrix with different chemical groups [ 68 , 91 , 92 ].…”
Section: Chitosan-based Nanosystem Of Smart Drug Delivery Systemmentioning
confidence: 99%